2013
DOI: 10.2478/rjes-2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

Academic Research Skills of University Students

Abstract: The paper analyzes questionnaires administered to 135 English Language students in all four years with an attempt to elaborate how developed the students’ academic research skills are and investigate if they correlate with the years of study. Furthermore, the results are compared to students’ general habits concerning internet use to prove that they do not correlate with academic research skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The results show that students perceive their DC as developed, which is in line with other research done with students from Serbia (e.g. Topalov et al, 2013). However, the same studies have shown that students conduct their search in a very limited manner and their knowledge of relevant and useful online resources is lacking.…”
Section: Discussionsupporting
confidence: 89%
“…The results show that students perceive their DC as developed, which is in line with other research done with students from Serbia (e.g. Topalov et al, 2013). However, the same studies have shown that students conduct their search in a very limited manner and their knowledge of relevant and useful online resources is lacking.…”
Section: Discussionsupporting
confidence: 89%
“…A systematic review found seven studies that evaluated research capabilities, three of which performed and reported on the psychometric validation of these instruments [ 10 ]. A study on philosophy students was conducted in Serbia, and the results show that students have difficulty using digital and virtual libraries [ 11 ]. A study on medical students in Sri Lanka discovered that 64% generated research ideas and 78% had difficulty conducting a literature review [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of research skills for many pedagogical professions commences in undergraduate education yet there is limited evidence regarding effective research teaching and learning approaches. According to (G. Rodríguez, N. Pérez, G. Núñez [1]; J. Topalov, B. Radić-Bojanić [2]) the main goal of recearch activity is to consolidate and to deepen knowledge which are received by students within the process of training, to acquire the necessary research skills. For most of this century, and increasingly in modern times, teacher educators have been impelled to consider ways in which a greater level of reflectivity, especially through enhancing research skills development, might be integrated into the teacher education program (T. Lovat, M. Davies, R. Plotnikoff [3]).…”
Section: Introductionmentioning
confidence: 99%